Association of cataract extraction and the risk of dementia—A systematic review and meta-analysis - Zhang, Qiao; Ju, Yuan; Zheng, Wei; Xie, Lulu; Wang, Xi; Ren, Huanhuan; Chen, Zhipeng; Liu, Xingtong; Bai, Xiaolin; Fan, Ruile (Frontiers in Aging Neuroscience, 2023)
Abstract Objectives :The aim of this study is to investigate if cataract extraction lowers the risk of all-cause dementia. Methods：Original literature on cataract surgery associated with all-cause dementia as of November 27, 2022, was searched in several commonly used databases.Eligible studies were included by manual review. The statistical analysis of pertinent data was performed using Stata software (version 16). Publication bias can be precisely evaluated by using funnel plots and the Egger’s test. Results: In the meta-analysis of 4 cohort studies with 245299 participants. Pooled analysis indicated that cataract surgery was linked to a lower incidence of all-cause dementia (OR=0.77, 95%CI: 0.66-0.89; I2=54.7%; P＜0.001) . cataract surgery was linked to a lower risk of AD (OR=0.60, 95%CI: 0.35-1.02; I2=60.2%; P＜0.001) . Conclusions：Cataract surgery is linked to a lower incidence of all-cause dementia and AD. Cataract is a reversible visual impairment. Cataract surgery may be a protective factor for the onset of all-cause dementia and can reduce the economic and family burden caused by all-cause dementia worldwide. Keywords:cataract, dementia, Alzheimer’s disease, meta-analysis, cohort study